Legend [compact disc] - Marley, Bob (Definitive remasters., 2002)
The best of the Jamaican reggae legend and one of the most important musicians of his era, this album features the real version of "I Shot the Sheriff," the hymnlike "No Woman, No Cry," and the sheer joy of "Jamming."